Handbook of material weathering - Wypych, George (ChemTec Pub., 1995)
A reference for those involved in studying material durability, producing materials for outdoor use and actinic exposure, research chemists in the photochemistry field, chemists and material scientists designing new materials, users of manufactured products, those who control the quality of manufactured products, and students who want to apply their knowledge to real materials. The information can be applied to such practical tasks as improved sample preparation methods or selection of conditions of weathering which increase the precision of studies. It can also be used to study material durability in depth since each subject is discussed from various angles of this multidisciplinary field.